Complications of Endoscopic Retrograde Cholangiopancreatography in Patients With Previous Bariatric Surgery: A National Inpatient Sample Analysis, 2007-2013. Issue 1 (January 2022) - Choi, Catherine; Barajas-Ochoa, Aldo; Xue, Pei; Hashemipour, Reza; Rotundo, Laura; Nasir, Umair; Jiang, Yi; Ahlawat, Sushil
Abstract : Background: Bariatric surgery (BS) has been proven to be effective in the treatment of obesity and weight-related diseases, but the anatomic changes after BS make endoscopic retrograde cholangiopancreatography (ERCP) technically challenging. This study aims to assess the safety and clinical outcomes of ERCP in patients with previous BS. Materials and Methods: The National Inpatient Sample from 2007 to 2013 was queried for hospitalizations of adults over 18 years of age with procedure diagnoses of ERCP. Those with prior BS were selected as cases and those without BS as controls. Case-control matching at a ratio of 1 case to 2 controls was performed based on sex, age, race, comorbidities, and obesity. The primary outcomes were inpatient mortality and ERCP-related complications. Multivariate regression analysis was used to identify independent risk factors associated to the primary outcomes. Results: A total of 1, 068, 862 weighted hospitalizations with ERCP procedure codes were identified. Of these, 6689 with BS were selected as cases, and 13, 246 were matched as controls. The reason for hospital admission was most often biliary stone disease (60.7% vs. 55.5%), followed by malignancy (3.5% vs. 12.1%) and cholangitis (7.7% vs. 4.5%) with and without BS, P <0.05. The BS group had lower rates of post-ERCP pancreatitis (0.1% vs. 1.3%), cholecystitis (0.1% vs. 0.3%), bleeding (1.0% vs. 1.4%), and inpatient mortality (0.2% vs. 0.5%), but had higher rates of cholangitis (5.0% vs. 3.7%) and systemic infections (6.2% vs. 4.8%), all P <0.05. Conclusions: BS group had lower post-ERCP pancreatitis, cholecystitis and bleeding while had more cholangitis, and systemic infection compared with those without BS. Also, BS was independently associated with reduced inpatient mortality after adjusted for age, race, and comorbidity.